Characterizing centrality: Obsidian consumption, supra-regional connectivity, and social reproduction at the Early Bronze Age sanctuary of Keros (Cyclades, Greece) - Tristan Carter; Rose Moir; Marina Milić; Colin Renfrew (PLoS ONE, 2025)
Early Bronze Age [EBA] Keros was a central place in the 3rd millennium cal BC Cycladic islands (Greece). Its material culture attests links with communities throughout the Aegean and beyond. This study uses obsidian sourcing to help reconstruct the socio-economic networks that coalesced at the site. Some 207 artifacts were elementally characterized using portable x-ray fluorescence spectroscopy [pXRF], the material coming from two ritual deposits in the Kavos area (n = 103), and the opposite islet settlement of Dhaskalio (n = 104). The results are consonant with the cosmopolitan character of Keros’ ceramic and metallurgical assemblages with not only the expected Melian sources of Dhemenegaki and Sta Nychia represented, but also handfuls of much rarer material from Giali A in the Dodecanese and East Göllü Dağ in central Anatolia. The study also provides further evidence for a Cycladic and Cretan preference for Sta Nychia raw materials in the EBA. A more complex picture of Melian obsidian consumption locally and regionally is then produced by integrating the sourcing data with the artifacts’ techno-typological and metrical attributes, which enables us to detail several EBA cultural traditions or ‘communities of practice’ across the Aegean region. The small quantities of Giali A and East Göllü Dağ obsidian are testimony to the supra-regional networks that coalesced at the site. Both raw materials likely circulated alongside the flow of Anatolian metals into the Aegean (including tin and gold), a network that introduced socially significant media and knowledge to Keros from as far east as the Indus. This congregation of people, resources, and technical know-how on Keros formed a key mode of social reproduction in Cycladic society with the mortuary and commemorative rituals on Kavos and the commensal gatherings on Dhaskalio comprising important spaces for the initiation, maintenance, and celebration of social relations.